A Safe Space Behind Revolving Doors: Opportunity Structures and the Multiple Layers of LGBTQ+ Business-Based Activism in a Hostile State - Valkovičová, Veronika; Schiffi, Camila (PARTECIPAZIONE E CONFLITTO, 2024)
Despite LGBTQ+ employee resource groups having become a commonly recognized initiative in Slovakia, research conducted within these groups in the Central and Eastern European region so far has been lacking. Existing literature from the Global North indicates that the groups and their members aim for a great diversity of objectives. We propose to study LGBTQ+ employee resource groups not only as business-based initiatives driven by human resources development, but also as collective actions within the theoretical framework of modern social movements that emphasize opportunity structures and movement resources. The present case study sheds light on the different levels of objectives aimed at by employee resource groups’ members, as they operate in specific organizational environments as well as in a country with widespread hetero/cis-sexism and growing political hostility. The case study indicates that it is the ability to operate at two institutional levels of opportunity structures that allows these groups to mitigate the costs of activism while at the same time allowing their engagement with the LGBTQ+ civil society in the country.